Effect of dough mixing with slightly acidic electrolyzed water on the shelf-life and quality characteristics of fresh wet noodles. (June 2021) - Xing, Jun-Jie; Jiang, Dong-Hui; Guo, Xiao-Na; Yang, Zhen; Zhu, Ke-Xue
Abstract: This study investigated the effect of dough mixing with slightly acidic electrolyzed water (SAEW) on the shelf-life and qualities of fresh wet noodles. The initial total plate count (TPC) of fresh wet noodles prepared with SAEW was decreased significantly ( p  < 0.05) and the shelf-life was extended to 5 days. The decrease of polyphenol oxidase activity of noodles was beneficial for browning inhibition purposes and the L* value of noodle sheets did increase after SAEW treatment. Higher SAEW concentration contributed to the increased hardness of fresh wet noodles. The increase of peak viscosity of fresh wet noodles and the closely related enhanced tensile force were mainly due to the chemical cross-linking effect of oxidized starch, which was resulted from the oxidation process during SAEW treatment. Furthermore, the polymerization of monomeric proteins induced by SAEW treatment was also evidenced by molecular weight distribution profiles of proteins and morphology changes in SAEW noodles. Highlights: Slightly acidic electrolyzed water (SAEW) improved the storage quality of noodles. SAEW treatment could inhibit microbial growth and extend shelf-life of noodles. SAEW dough mixing could be used for browning inhibition purpose in fresh noodles. The hardness and tensile force of cooked SAEW noodles were increased. Both starch oxidation and protein polymerization happened during SAEW treatment.